Rapid and Sensitive Determination of HIV-1 Virus Based on Surface Enhanced Raman Spectroscopy - Lee, Jin-Ho; Kim, Byung-Chan; Oh, Byeung-Keun; Choi, Jeong-Woo (AMER SCIENTIFIC PUBLISHERS, 2015)
In this study, rapid and sensitive detection of human immunodeficiency virus (HIV)-1 was performed based on immunoreactions with an Au nanodot fabricated indium tin oxide (ITO) substrate using surface-enhanced Raman spectroscopy (SERS). Highly ordered Au nanodots (ca. 20 nm) were electrochemically fabricated over a large surface area (20 mm x 10 mm) of an ITO substrate using a simple deposition method with Triton X-100. On the Au nanodot surface, monoclonal antibody fragments against gp120 were selectively bound by gold-sulfur interactions. Various concentrations (35 fg/mL to 350 pg/mL) of HIV-1 virus-like particles (HIV-1 VLPs) were used for the measurements. The presence of HIV-1 VLPs was rapidly (within 5 s) and successfully determined by SERS due to specific immunoreactions on the Au nanodots without the use of labeling probes. The results showed the possibility of using SERS-related methods as a new immunoassay for the study of biomolecular interactions and detection of low viral loads. Moreover, based on its high sensitivity and chemical specificity, SERS could be used as a promising clinical tool for detecting infectious small biological components.
Keywords: PLASMON RESONANCE; VIBRATIONAL ANALYSIS; SILVER ELECTRODE; PROTEINS; RNA; NANOPARTICLES; IMMUNOSENSOR; POLYPEPTIDES; ANTIBODIES; INFECTION